Bruxism as a cause of tooth wear: a demanding physiological activity on the modern human stomatognathic system - Assis, Miguel (2024)
Mastication is commonly considered the primary function of the stomatognathic system, and more specifically of the teeth. Studies conducted in the 70s and early 80s revealed that there is almost no contact between teeth during mastication when the bolus is interposed between the dental surfaces, except in the phase of maximum intercuspation. Although mastication is based on an automated muscle activation pattern, it is still a conscious activity. Tooth wear is mostly attributed to abrasion caused by the hardest components of food or by contaminating abrasive materials, such as silica or carbonates. The use of teeth as a tool is also considered a common cause of tooth wear. Differently from mastication, sleep bruxism is an unconscious excursive movement of the lower teeth, which uses the full length of the dental guiding path, and is performed with greater muscular force and in the absence of an interposed bolus. Thus, it might result in heavy tooth contact leading to conspicuous loss of dental material. Since recent modern humans rely on a soft and refined diet, which does not generally account for tooth wear, the possibility of bruxism as a major factor contributing to dental material loss should not be dismissed. In this light, tooth wear patterns in modern-day subjects and past populations should be addressed on the basis of the clinical experience allowing the assessment of bruxism and chewing activities in living subjects. In this paper, clinical know-how on bruxism and the resulting dental wear in contemporary industrialized societies is presented as a possible source of information to be integrated into the most common notion of dental wear in anthropology.